Bioactive Compounds and Biological Activities of Yacon Root (Smallanthus sonchifolius) on Gut-Liver-Adipose Tissue Axis - Romualdo, Guilherme Ribeiro [UNESP]; de Souza, Isadora Penedo [UNESP]; da Rocha Viana, José Diogo; Dionísio, Ana Paula; Barbisan, Luís Fernando [UNESP] (Springer Nature, 2024)
Yacon (Smallanthus sonchifolius) is a perennial plant native to the Andean region of South America. It has gained attention for its tuberous roots, which are a rich source of bioactive compounds, such as fructooligosaccharides and phenolic compounds. Accumulating recent (pre)clinical data indicate that yacon possesses several notable biological properties that make it a plant with increasing market value. Thus, the objective of this chapter is to offer a comprehensive summary of the primary biological effects of yacon, along with a brief introduction to its origins, utilization, and diverse bioactive compound profile. Data indicate that the high content of fructooligosaccharides in yacon roots contributes to its prebiotic nature, promoting the growth of beneficial gut bacteria, supporting digestive health, and preventing colorectal cancer. Furthermore, the presence of phenolic compounds, such as chlorogenic acid, offers antioxidant and anti-inflammatory benefits. Further investigation may enable valuable insights on yacon’s potential clinical applications, and inspire the development of yacon-based products, including functional foods, nutraceuticals, and pharmaceuticals.
Keywords: Anti-inflammatory; Antioxidant; Bioactive compounds; Cancer-preventive activity; Fructooligosaccharides; Polyphenols·prebiotic; Smallanthus sonchifolius; Yacon